Integrating Historical Pesantren Eduliterature Flipbooks in EFL Reading Learning - Aang Fatihul Islam; Rukminingsih Rukminingsih; Mochamad Fadillah Abdullah; Hidayatul Lailina (Lembaga Bale Literasi, 2026)
The integration of digital technology and local wisdom-based learning materials has become increasingly important in English as a Foreign Language (EFL) instruction in Indonesia. However, relatively limited studies have explored the integration of pesantren eduliterature into digital reading materials within Islamic educational contexts. This study investigates Indonesian EFL teachers’ and students’ perceptions of Historical Pesantren Eduliterature reading materials delivered through interactive flipbook applications. Employing an explanatory mixed-method survey design, the study involved 71 participants consisting of teachers and students from several Islamic educational institutions in East Java, Indonesia. Data were collected through Likert-scale questionnaires and open-ended responses and were analyzed using descriptive statistics and thematic analysis. The findings indicate that participants held highly positive perceptions toward the Historical Pesantren Eduliterature Flipbooks, with an overall mean score of 4.33 out of 5. Cultural relevance received the highest rating (M = 4.54), followed by reading motivation (M = 4.42), interactive learning experience (M = 4.31), and multimedia support (M = 4.28). Qualitative findings revealed three major benefits: enhanced reading motivation, stronger cultural and religious connection to learning content, and increased learner autonomy through multimedia features such as annotation tools, dictionaries, and adjustable displays. Despite these advantages, participants reported challenges related to unequal digital literacy, limited technological infrastructure, and insufficient institutional support. The study highlights the pedagogical potential of integrating local wisdom, historical literacy, and digital learning platforms in EFL reading instruction. The findings contribute to the growing body of research on culturally responsive digital learning materials and offer practical implications for the development of contextualized English teaching resources in Indonesian Islamic educational settings.